Chemical composition of \(Elsholtzia ciliata\) (Thunb.) Hyland essential oil in Vietnam with multiple biological utilities: a survey on antioxidant, antimicrobial, anticancer activities - Luu Tang Phuc, Khang; Nguyen, Huu Tai; Cao, Van Len; Nguyen, Ngoc Thu Phuong; Nguyen, Hoang Viet; Truong, Vinh; Phan, Thanh Bach; Phuong Dung, Tran Thi; Xuan Tong, Nguyen (Academia Journal of Biology, 2023)
Elsholtzia ciliata (Thunb.) Hyland is commonly known as Vietnamese balm - a spicy, lemon-scented culinary herb in Asian cuisine, especially in Vietnam. The biological activities of E. ciliata essential oils (Ec EOs) in Vietnam have yet to be thoroughly studied and have received less attention than other species of genus Elsholtzia in the world. In this study, we evaluated the antioxidant, antimicrobial, and anticancer of Ec EOs and examined their chemical compositions. Fresh leaves of E. ciliata were hydro-distilled to yield essential oil of 0.82% dry weight, respectively. Gas chromatography-mass spectrometry (GC-MS) analyses revealed that Ec EOs principally possessed complex mixtures of monoterpenes and sesquiterpenes. (Z)-β-Farnesene (22.72%), neral (15.66%), geranial (15.62%), and β-ocimene (13.30%) were the major components of Ec EOs. In the antioxidant assay, the radical scavenging capacities of Ec EOs against DPPH were 26.55 g/L (IC50). In the antimicrobial assay, the evaluation of antimicrobial activity using the agar wells diffusion method showed that Ec EOs in all concentrations was active against the Gram-positive bacteria (Bacillus cereus, Bacillus subtilis, Staphylococcus aureus), Gram-negative bacteria (Proteus mirabilis, Escherichia coli, Klebsiella pneumoniae). In the anticancer assay, EcE Os can be toxic to Hep G2 cells with IC50 reaching 0.00204%.